Analisis Pengaruh Bauran Pemasaran terhadap Penjualan - Sopiana, Nana (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2021)
The purpose of this study is to prove the significance of the influence of the marketing mix both simultaneously and partially on the sale of coffee products and prove the marketing mix that has a dominant influence on the sale of coffee products in coffee companies and convection "Aneka Busana" Kediri West Lombok. The type of research used to examine the above problems is descriptive research with case study method. The analytical tools used in this study are multiple linear regression analysis, hypothesis test (f test), hypothesis test (t test), and classic assumption test processed through SPSS program. The results showed that: (1) For the F test hypothesis test, that together product variables, prices, promotions, distributions influenced sales so that Ho was rejected and Ha accepted; (2) For the test hypothesis test t , which does not have a significant influence on sales is a variable promotion and distribution channel; (3) Of the four variables that have a dominant influence on sales is the price variable